Reflexión sobre la importancia del actor psicológico en la reducción de deserción estudiantil - Aguirre Flores, Vanessa (2016)
Dropout is a multifactorial phenomenon occurring both at the school and at the higher level. This phenomenon is a problem that must concern all those involved in the educational area, as well as the state because of the losses it causes. This article refers the factors that affect desertion, giving greater emphasis to the psychological factor as one of the main predictors of this phenomenon. So, a reflection is made on how relevant it is to address this predictor of desertion, and thus achieve reduction of their indexes, proposing actions that allow students to successfully face the  changes involved in the beginning of a  newstage as is higher education.